Deteksi Fraud pada LKM Syariah: Tinjauan Internal Control dan Budaya Organisasi - Cinda Nongfasya Ruwary; Mukhtaruddin Mukhtaruddin (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
The sustainability of Islamic Microfinance Institutions (IMFIs) is increasingly threatened by fraud, yet existing mitigation strategies often over-rely on "hard controls" like Internal Control Systems (ICS). This study aims to reconstruct a holistic detection model by bridging technical audits with behavioral-spiritual approaches. Using a Systematic Literature Review (SLR) of 26 articles and the Fraud Diamond Theory as an analytical framework, this research challenges the effectiveness of procedural compliance alone. The findings reveal that while integrating AI-driven technical audits is vital to eliminate Opportunity in real-time, it remains inadequate without "soft controls." Islamic Organizational Culture is identified as a critical immunity that neutralizes the Rationalization and Pressure arising from the "double bottom line" conflict. Furthermore, the study establishes that a dual governance mechanism synchronizing financial and Sharia audits is required to mitigate perpetrator capability significantly. This synergy ensures that fraud detection extends beyond financial manipulation to include Sharia non-compliance, thereby safeguarding Maqasid Sharia, particularly the protection of wealth (hifz al-mal), from systemic erosion.